2006
DOI: 10.1111/j.1460-9568.2006.04902.x
|View full text |Cite
|
Sign up to set email alerts
|

The septal EEG suggests a distributed organization of the pacemaker of hippocampal theta in the rat

Abstract: Individual neurons in the medial septum and diagonal band fire in phase with, and appear to act as a 'pacemaker' of, the hippocampal theta rhythm. We investigated the relationships of periodic EEG both among various parts of the septum and with dorsal hippocampal theta recorded concurrently in freely moving rats. Most septal sites showed theta rhythm concurrent with hippocampal theta during locomotion. However, periods with theta at hippocampal but not septal sites were more frequent than the reverse. Theta wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…Indeed, while there is both old and new evidence for the importance of septal glutamate, GABA and ACh neurons in regulating hippocampal activity and locomotion, navigation and exploration (Fuhrmann et al 2015), septal theta does not always precede hippocampal theta, suggesting that regulation of hippocampal theta activity is better viewed as occurring via a set of functionally interrelated components than via a single entity (Nerad and McNaughton 2006). A better understanding of how septal systems integrate the complex brainstem and telencephalic inputs/functions can be obtained by documenting the cytoarchitectonics and related circuits of the septum.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, while there is both old and new evidence for the importance of septal glutamate, GABA and ACh neurons in regulating hippocampal activity and locomotion, navigation and exploration (Fuhrmann et al 2015), septal theta does not always precede hippocampal theta, suggesting that regulation of hippocampal theta activity is better viewed as occurring via a set of functionally interrelated components than via a single entity (Nerad and McNaughton 2006). A better understanding of how septal systems integrate the complex brainstem and telencephalic inputs/functions can be obtained by documenting the cytoarchitectonics and related circuits of the septum.…”
Section: Discussionmentioning
confidence: 99%
“…This view was strengthened by more recent EEG recordings in freely-moving rats that demonstrated that the integrity of the entire medial and lateral septum-hippocampal network is critical for the generation of theta rhythm (Nerad and McNaughton, 2006). There has also been a consensus over many years that the different types of neurons in the septal area play specific roles in generating theta synchrony, with slow-firing cholinergic neurons facilitating hippocampal firing, and parvalbumin GABAergic neurons that innervate GABAergic hippocampal interneurons driving disinhibition of pyramidal or granule cell inhibition, allowing hippocampal synchrony (Freund and Antal, 1988;Freund and Gulyas, 1997;Toth et al, 1997a;Wu et al, 2000), although more recent studies have questioned the relative importance of different neuron populations in awake animals (e.g.…”
Section: Introductionmentioning
confidence: 92%
“…Because many of these MS/DB GABA neurons are known to project to the hippocampus (Jones et al, 1999;Sotty et al, 2003), they may contribute significantly to the generation and/or modulation of hippocampal theta (Toth et al, 1993). In addition, recent results surprisingly showed that hippocampal theta may be initiated significantly more often in hippocampus than in septum (Nerad and McNaughton, 2006). Therefore, it is possible that local hippocampal theta activity may trigger resonating (I h expressing) MS/DB neurons, which in turn modulates and/or helps generate theta across the hippocampus.…”
Section: H Current Is Important In Hippocamposeptal Synchronizationmentioning
confidence: 99%